Registered nurses' awareness and implementation of reasonable adjustments for people with intellectual disability and/or autism. (7th February 2022) - Wilson, Nathan J.; Pracilio, Amy; Kersten, Michelle; Morphet, Julia; Buckely, Thomas; Trollor, Julian N.; Griffin, Ken; Bryce, Julianne; Cashin, Andrew
Abstract: Aim: To describe Australian registered nurses' awareness, and implementation of reasonable adjustments within their practice when caring for people with intellectual disability and/or autism. Additionally, the association between key demographic, workforce, and respondent variables and familiarity of the term and regularity of use was explored. Design: Cross‐sectional survey. Methods: Survey data were collected between August and October 2020 using an online survey tool. Data were analysed using descriptive and inferential statistics. Results: Familiarity of the concept of reasonable adjustments was relatively low, compared to respondents who report applying adjustments when caring for people with intellectual disability and/or autism. Higher levels of confidence, comfort, and knowledge when caring for this cohort were associated with greater awareness and application of reasonable adjustments. Conclusion: A higher volume, and diversity in type of, nursing education related to care for people with intellectual disability and/or autism is indicated.